CARBONO E NUTRIENTES NA BIOMASSA E NO SOLO EM POVOAMENTO DE Anadenanthera peregrina (L.) Speg. var. peregrina EM DIFERENTES ESPAÇAMENTOS - Gomes, Robert (2022)
The study aimed to describe changes in soil attributes and evaluate the effect of planting spacing on soil carbon and nitrogen stocks, aboveground biomass and nutrients, as well as nutrient use efficiency in Anadenanthera peregrina (L.) Speg. var. peregri